Local Finance and Regional Expenditures: Is There a Flypaper Effect in Indonesia? - Firda Rahmasari, Try; Darmastuti, Dewi; Ardhi Nurrahman, Khalid (KnE Social Sciences, 2024)
The granting of authority based on regional autonomy should be able to create local government independence to manage their own finances through local own-source revenue and promote sustainable economic growth. However, many previous studies have found the flypaper effect phenomenon in Indonesia. This research aims to determine the effect of local own-source revenue, intergovernmental transfers, and local government financing on local government expenditure and detect the flypaper effect phenomenon in Indonesia. This quantitative method with a purposive sampling technique has been used to obtain data from 467 regencies/cities in Indonesia for the fiscal year 2021. Hypothesis testing in this research employs multiple linear regression analysis. The research result shows local own-source revenue, general allocation fund, special allocation fund, and revenue sharing fund do not affect local government expenditure, and local government financing positively affects local government expenditure. This research did not find the flypaper effect in local governments in Indonesia but identified other funding mechanisms to meet the needs of local government expenditure derived from local government financing. Keywords: flypaper effect, local own-source revenue, intergovernment transfers, local government financing, regional expenditures